2021
DOI: 10.1038/s41598-021-93527-8
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous misfolded protein oligomers can cross the intestinal barrier and cause a disease phenotype in C. elegans

Abstract: Misfolded protein oligomers are increasingly recognized as highly cytotoxic agents in a wide range of human disorders associated with protein aggregation. In this study, we assessed the possible uptake and resulting toxic effects of model protein oligomers administered to C. elegans through the culture medium. We used an automated machine-vision, high-throughput screening procedure to monitor the phenotypic changes in the worms, in combination with confocal microscopy to monitor the diffusion of the oligomers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 94 publications
(196 reference statements)
0
9
0
Order By: Relevance
“…In contrast, our study uses biochemically well-defined aggregated species of α-synuclein as the initial seed, and demonstrates the induction of aggregation of host α-synuclein in a prion-like manner. In a recent study in which α-synuclein oligomers were fed to C. elegans and were able to cross the intestinal barrier and cause toxicity ( 28 ), the worms lacked host α-synuclein and thus these are not models of prion-like α-synuclein activity but rather provide insights into non-prion–like mechanisms of α-synuclein–initiated disease. In our models, we found that later time-points after PFF feeding, or exposure to high PFF concentrations, resulted in non-prion–like phenotypes in which monomeric α-synuclein treatment was similarly toxic to PFFs, and the phenotypes were not progressive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, our study uses biochemically well-defined aggregated species of α-synuclein as the initial seed, and demonstrates the induction of aggregation of host α-synuclein in a prion-like manner. In a recent study in which α-synuclein oligomers were fed to C. elegans and were able to cross the intestinal barrier and cause toxicity ( 28 ), the worms lacked host α-synuclein and thus these are not models of prion-like α-synuclein activity but rather provide insights into non-prion–like mechanisms of α-synuclein–initiated disease. In our models, we found that later time-points after PFF feeding, or exposure to high PFF concentrations, resulted in non-prion–like phenotypes in which monomeric α-synuclein treatment was similarly toxic to PFFs, and the phenotypes were not progressive.…”
Section: Discussionmentioning
confidence: 99%
“…In our models, we found that later time-points after PFF feeding, or exposure to high PFF concentrations, resulted in non-prion–like phenotypes in which monomeric α-synuclein treatment was similarly toxic to PFFs, and the phenotypes were not progressive. It is possible that mechanisms engaged in these contexts might be similar to the non-prion–like events induced by exogenous oligomers in worms lacking α-synuclein ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of the neuromuscular dysfunction caused by tau assemblies remain to be elucidated. We hypothesized that similarly to oligomers of other misfolded proteins, tau oligomers too, once ingested by C. elegans , can be absorbed by the gut and diffuse in various tissues, affecting neuromuscular function [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…We then investigated whether this cell-worm-based approach can be applied to studies aimed at discovering drugs to interfere with tau oligomeric toxicity. C. elegans has already been proposed as a valuable in vivo model for screening of compounds against different protein misfolding diseases [19,30] and the observations from these studies have already been translated into clinical applications [19,31].…”
Section: Discussionmentioning
confidence: 99%